IDENTIFIKASI LOKASI PRIORITAS UNTUK PEMBANGUNAN AKUIFER BUATAN SIMPAN AIR HUJAN (ABSAH) DI WILAYAH SUNGAI CITANDUY, JAWA BARAT - Priandani, Fabian (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Artificial Aquifer and Rain Storage Structure (AARSS) is a rainwater harvesting technology developed by the Research Center for Water Resources, Ministry of Public Works and Housing. It utilizes rainwater that is stored in a reservoir and flows through an artificial aquifer. The study aims to identify the priority of locations for AARSS development in the Citanduy River Basin. The method used is a weighted overlay using the Analytical Hierarchy Process and Geographic Information System. A map of priority locations is obtained using 6 biophysical and socio-economic parameters: rainfall, land use/land cover, the presence of groundwater basins, drought-prone classes, village development, and construction costs represented by the minimum wage. The priority of priority locations is classified into very high-, high-, medium-, low-, and very low priority zones. The analysis result shows the domination of the medium priority zone (63.73% of the study area), which is followed by the high, low, very high, and very low priorities with the percentage of 24.03%, 8.49%, 3.58%, and 0.17%, respectively. An evaluation of the current AARSS constructions to this priority map shows that there are 8 AARSS units in the medium-, 7 units in the high-, and 2 units in the very high priority zone. The priority map can be used by decision-makers to identify an optimal location and develop a suitable structure that meets the water-demand of their community. This study can serve as a comparison for research related to site identification for rainwater storages in other areas.Keywords: Artificial Aquifer and Rain Storage Structure (AARSS), site identification, rainwater harvesting, analytical hierarchy process, geographic information system